1983
DOI: 10.1126/science.6683427
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Brain Transplant: Reduction of Cognitive Deficits in Rats with Frontal Cortex Lesions

Abstract: Frontal cortex and cerebellar tissue from fetal rats was implanted into the damaged frontal cortex of adults. Cognitive deficits in spatial alternation learning that follow bilateral destruction of medial frontal cortex were reduced in rats with frontal cortex implants but not in those with implants of cerebellum. Histological evaluation showed that connections were made between the frontal cortex implants and host brain tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
3

Year Published

1984
1984
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(63 citation statements)
references
References 15 publications
4
56
3
Order By: Relevance
“…Rats with transplants of E19 frontal cortex tissue into the lesioned cortex showed significant recovery in DSA, compared with lesion-only controls, 5 d after the operation. Such rapid recovery could be attributed to the release of trophic or other factors from the transplants into the host rather than through the formation of new transplant-host interconnections, which would not occur so rapidly (Labbe, 1983;Stein, 1988;Stein and Glasier, 1995). In an additional supporting study, Stein (1988) removed the transplants in one group of rats and found that the performance on DSA 3 months after surgery was not impaired in these rats.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Rats with transplants of E19 frontal cortex tissue into the lesioned cortex showed significant recovery in DSA, compared with lesion-only controls, 5 d after the operation. Such rapid recovery could be attributed to the release of trophic or other factors from the transplants into the host rather than through the formation of new transplant-host interconnections, which would not occur so rapidly (Labbe, 1983;Stein, 1988;Stein and Glasier, 1995). In an additional supporting study, Stein (1988) removed the transplants in one group of rats and found that the performance on DSA 3 months after surgery was not impaired in these rats.…”
Section: Discussionmentioning
confidence: 88%
“…For example, Stein and colleagues (Labbe, 1983;Stein, 1988) showed that lesions of the frontal cortex in adult rats lead to an impairment in a delayed spatial alternation T-maze task (DSA). Rats with transplants of E19 frontal cortex tissue into the lesioned cortex showed significant recovery in DSA, compared with lesion-only controls, 5 d after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the trophic graft mechanisms in other transplant models may account for some graft effects (38)(39)(40), available rodent models of HD show that the implanted striatal neurons can substitute for the damaged striato-pallidal neuronal connections (23)(24)(25)(26)(27). Physiological (15)(16)(17), neurochemical (41,42), and anatomical studies (23)(24)(25)(26)(27) suggest that a partial restoration of striatal input and output circuitry by implanted striatal neurons can occur.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioral deficits associated with damage to the nigrostriatal system, fimbria-fornix or frontal cortex have been reported to be diminished by implanting fetal dopaminergic neurons, fetal septal or frontal cortical tissue, respectively, into the lesion sites (Bjorklund and Stenevi, 1979b;Dunnett et al, 1982;Labbe et al, 1983). In recent experiments by Gage et al (1983), transplantation of dopaminergic neurons from the fetal substantia nigra into the caudate-putamen of old rats effectively restored age-dependent decline in motor coordination.…”
Section: Recovery O F Declined Ovarian Function In Agedmentioning
confidence: 99%